Insight into the Mechanism for the Emergence of Thermally Stable Reflection Colors from Cholesteric Liquid Crystals of Etherified Ethyl Cellulose Derivatives and Methacrylic Acid - Wakako Kishi; Naoto Iwata; Seiichi Furumi (Molecules)
Ethyl cellulose (EC) and its derivatives are known to exhibit the cholesteric liquid crystal (CLC) phase with visible light reflection in a lyotropic manner after adding appropriate solvents. Generally, the reflection peak of conventional CLCs is easily wavelength shifted by temperature. However, our previous study showed that the reflection wavelength can be maintained even after heating for the lyotropic CLCs of completely pentyl-etherified EC derivatives with methacrylic acid (MAA). However, the emergence of thermally stable reflection colors still remains obscure in the mechanism at the mesoscopic scale. In this study, we evaluated the temperature dependence of the reflection wavelength for the lyotropic CLCs of a series of completely etherified EC derivatives possessing different alkoxy chains by addition of MAA. It was found that butyl- or pentyl-etherified EC derivatives are suitable for preparation of the lyotropic CLCs with visible Bragg reflection, whereas visible light reflection cannot be observed for the other mixtures of propyl- and hexyl-etherified EC derivatives with MAA. Furthermore, it turned out that lyotropic CLCs of pentyl-etherified EC derivatives with MAA show the smallest temperature dependence of their reflection wavelength. Based on the results of ultra-small-angle X-ray scattering (USAXS) and small-angle X-ray scattering (SAXS) measurements of CLC films, we presumed that the emergence of thermally stable reflection colors from the lyotropic CLCs of pentyl-etherified EC derivatives with MAA arises from their phase separation at the mesoscopic scale by changing the temperature.